The effect of the China Shock on portuguese employment at the firm-level - Casimiro, Gonçalo de Castro Navarro Raimundo (2021)
This paper expands the analysis of the effects of the China shock by assessing its positive effects via access to cheaper inputs and contrasting them with the negative effects through increased import competition in the output markets. We use longitudinal matched employer-employee data linked with customs firm-level data on outputs and inputs transactions for the 1995-2007 period. We find economically and statistically significant positive effects on employment arising from an increase in imports of inputs from China and non-significant effects on employment arising from an increase in imports of outputs from China. Both ordinary least squares regressions and an instrumental-variable strategy using the change in China’s share of U.S. imports by input and output indicate a positive and significant effect of the China input shock and a non-significant effect of the China output shock. As a placebo, we replicate the analysis for the period before the China shock (1995-2000) finding non-significant impact on Portuguese employment. Regarding firms’ adjustment mechanisms, we find that in response to this shock, firms adapted their temporary employment levels rather than adapting their permanent employment levels.